Twilight people : one man's journey to find his roots - Houze, David, 1965- (University of California Press, 2006)
Triggers a journey of self-discovery and reconnection that ranges from the shores of South Africa to the dirty roads of Mississippi - and back. This narrative uses the unraveling mystery of Houze's family and his quest for identity as a prism through which to view the tumultuous events of the civil rights movement in Mississippi.
"The George Gund Foundation imprint in African American studies."
Keywords: Houze, David, -- 1965-; African Americans -- Biography.; African Americans -- Civil rights -- Southern States -- History -- 20th century.; Civil rights movements -- Southern States -- History -- 20th century.; Southern States -- Race relations.; Apartheid -- South Africa.; South Africa -- Race relations.; Siblings.; Sibling Relations; Noirs américains -- Biographies.; Noirs américains -- Droits -- États-Unis (Sud) -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- États-Unis (Sud) -- Histoire -- 20e siècle.; États-Unis (Sud) -- Relations raciales.; Apartheid -- Afrique du Sud.; Afrique du Sud -- Relations raciales.; Frères et sœurs.; siblings (people); TRAVEL.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Social History.; African Americans; African Americans -- Civil rights; Apartheid; Siblings; Civil rights movements; Race relations; South Africa; Southern States; 1900-1999; Autobiography; Biography; autobiographies (literary works); Autobiographies; Biographies; History; Autobiographies.; Biographies.